Immune Response and Partial Protection against Heterologous Foot-and-Mouth Disease Virus Induced by Dendrimer Peptides in Cattle - I. Soria; V. Quattrocchi; C. Langellotti; M. Pérez-Filgueira; J. Pega; V. Gnazzo; S. Romera; J. Schammas; D. Bucafusco; S. Di Giacomo; Beatriz G. de la Torre; D. Andreu; et al. (Journal of Immunology Research)
Synthetic peptides mimicking protective B- and T-cell epitopes are good candidates for safer, more effective FMD vaccines. Nevertheless, previous studies of immunization with linear peptides showed that they failed to induce solid protection in cattle. Dendrimeric peptides displaying two or four copies of a peptide corresponding to the B-cell epitope VP1 [136–154] of type O FMDV (O/UKG/11/2001) linked through thioether bonds to a single copy of the T-cell epitope 3A [21–35] (termed B2T and B4T, resp.) afforded protection in vaccinated pigs. In this work, we show that dendrimeric peptides B2T and B4T can elicit specific humoral responses in cattle and confer partial protection against the challenge with a heterologous type O virus (O1/Campos/Bra/58). This protective response correlated with the induction of specific T-cells as well as with an anamnestic antibody response upon virus challenge, as shown by the detection of virus-specific antibody-secreting cells (ASC) in lymphoid tissues distal from the inoculation point.